The Influence of Psychological Empowerment on Workforce Agility in Employees: A Lesson in Improving Human Resource Quality - Fadhila Berliana Cahya Asih; Umi Anugerah Izzati (Journal of Educational Management Research, 2026)
Dynamic changes in government policies and public assignments require employees of State-Owned Enterprises (BUMN) with Public Service Obligations to demonstrate a high level of adaptive capacity. This condition positions workforce agility as an important capacity in supporting work effectiveness within a continuously changing bureaucratic environment. This study aims to examine the effect of psychological empowerment on workforce agility within a public sector organization characterized by policy driven task dynamics. The study employed a quantitative method with a simple linear regression design. The research participants were 82 employees of BUMN X, collected using a convenience sampling technique. The results indicate that psychological empowerment has a significant effect on workforce agility, with a coefficient of determination of 0.292, indicating a moderate strength of influence. These findings suggest that strengthening psychological empowerment can serve as a strategic basis for human resource policies, employee development programs, and managerial practices aimed at enhancing workforce agility in BUMN organizations with public service mandates